Laser-induced p- and n-type graphene composites for flexible electronics - Petrov I. S. Iljya Sergeevich; Cheshev D. L. Dmitry Leonidovich; Kaprov S. A. Sergey Alekseevich; Vasileva F. Fedora; Rodriguez (Rodriges) Contreras R. D. Raul David; Sheremet E. S. Evgeniya Sergeevna (2025, 2025)
Title screen